Parenting Styles and Academic Achievement among Malaysian Students: Mediating Role of Parental Involvement - Mian Mian, Seet; Mohtaram, Rabbani; Simin, Hosseinian; Ravindran, Latha; Shanthi Bavani V, Rajan Mohan (UNIMAS Publisher, 2022)
The goal of the study is to see how parental participation affects the relationship between parenting styles and academic success in Malaysian primary school students. A quantitative technique was applied in this investigation. Private tuition centres in an urban area were used to recruit students. The information gathered for this investigation was numerically assessed and interpreted. Families are divided into four groups by the Parenting Style Index: authoritative, authoritarian, permissive, and indulgent. The relationship between parenting styles and academic success was studied using Pearson's correlation coefficient matrix. It was discovered that it completely mediates the relationship between authoritative and authoritarian parenting styles and student academic attainment. The study's findings show that understanding and receiving knowledge about how parenting styles and parental involvement affect children's academic achievement is crucial for parents.